PHYSICAL, PHYSIOLOGICAL, AND NUTRITIONAL CHARACTERIZATION OF SOYBEAN SEEDS AND CANONICAL INTERRELATIONS - Gabriel M. W. Bruinsma; Ivan R. Carvalho; Leonardo C. Pradebon; Amauri De Carli Alchieri; Murilo V. Loro; Willyan J. A. Bandeira; João P. Dalla Roza; Ivandro Reolon (Engenharia Agrícola)
ABSTRACT Technological advances in soybean (Glycine max L.) cultivation, particularly with Xtend technology cultivars, require appropriate and conscious management practices. This study aimed to identify canonical interrelationships among the physical, physiological, and nutritional parameters of soybean seeds carrying the DMO gene, using dicamba applied in both pre- and post-emergence stages. The experiment was conducted in Augusto Pestana, RS, Brazil, during the 2022/2023 growing season. Treatments consisted of eight dicamba application timings (pre- and post-emergence) across five Xtend cultivars. After harvesting, seed physical traits (diameter, circumference, perimeter, and area), germination, seedling viability, and seed nutritional components were evaluated. Seed diameter, perimeter, and area varied among cultivars, and reductions in these traits were associated with lower nutritional quality. Dicamba applications during the vegetative stages caused less damage to the physiological and nutraceutical quality of the seeds.